Zebrafish Models for Human Skeletal Disorders - Marí-Beffa, Manuel; Mesa-Román, Ana B.; Duran, Ivan (Frontiers in Genetics, 2021)
In 2019, the Nosology Committee of the International Skeletal Dysplasia Society provided an updated version of the Nosology and Classification of Genetic Skeletal Disorders. This is a reference list of recognized diseases in humans and their causal genes published to help clinician diagnosis and scientific research advances. Complementary to mammalian models, zebrafish has emerged as an interesting species to evaluate chemical treatments against these human skeletal disorders. Due to its versatility and the low cost of experiments, more than 80 models are currently available. In this article, we review the state-of-art of this “aquarium to bedside” approach describing the models according to the list provided by the Nosology Committee. With this, we intend to stimulate research in the appropriate direction to efficiently meet the actual needs of clinicians under the scope of the Nosology Committee.